A systematic review of the evidence supporting post-operative medication use in congenital heart disease. (19th May 2021) - Thompson, Elizabeth J.; Foote, Henry P.; King, Caitlin E.; Srinivasan, Sabarish; Ciociola, Elizabeth C.; Leung, Dennis; Rotta, Alexandre T.; Hill, Kevin D.; Cohen-Wolkowiez, Michael; Hornik, Christoph P.
Abstract: Background: Targeted drug development efforts in patients with CHD are needed to standardise care, improve outcomes, and limit adverse events in the post-operative period. To identify major gaps in knowledge that can be addressed by drug development efforts and provide a rationale for current clinical practice, this review evaluates the evidence behind the most common medication classes used in the post-operative care of children with CHD undergoing cardiac surgery with cardiopulmonary bypass. Methods: We systematically searched PubMed and EMBASE from 2000 to 2019 using a controlled vocabulary and keywords related to diuretics, vasoactives, sedatives, analgesics, pulmonary vasodilators, coagulation system medications, antiarrhythmics, steroids, and other endocrine drugs. We included studies of drugs given post-operatively to children with CHD undergoing repair or palliation with cardiopulmonary bypass. Results: We identified a total of 127 studies with 51, 573 total children across medication classes. Most studies were retrospective cohorts at single centres. There is significant age- and disease-related variability in drug disposition, efficacy, and safety. Conclusion: In this study, we discovered major gaps in knowledge for each medication class and identified areas for future research. Advances in data collection through electronic health records, novel trial methods, and collaboration can aid drug development efforts in standardising care, improving outcomes, and limiting adverse events in the post-operative period.